The terror of history mystics, heretics, and witches in the western tradition - Ruiz, Teofilo F., 1943-; Teaching Company (Chantilly, VA : Teaching Co., 2002)
This set of twenty-four lectures examines aspects of elite and popular culture in late medieval and early modern Western Europe, focusing on the way in which men and women seeking to explain, order, and escape the terrors of their lives embraced transcendental religious experiences, dreamed of and worked for the coming of the apocalypse, and seized on a widespread belief in witchcraft and Satanism.
part II. disc 3. lecture 13. Jewish millennial expectations ; lecture 14. The mysteries of the Renaissance ; lecture 15. Hermeticism, astrology, alchemy, and magic ; lecture 16. The origins of witchcraft ; lecture 17. Religion, science, and magic ; lecture 18. The witch craze and its historians -- disc 4. lecture 19. Fear and the construction of Satan ; lecture 20. The witch craze and misogyny ; lecture 21. The world of witches ; lecture 22. The witches of Loudon ; lecture 23. The witches of Essex and Salem ; lecture 24. The survival of the past.
Course consists of 2 parts. Each part includes 2 videodiscs and 1 course guidebook.
"Licensed for private home exhibition only."
Lecturer: Teofilo F. Ruiz.
DVD, region 1.
Keywords: Civilization, Medieval; Witchcraft -- Europe -- History; Mysticism -- Europe -- History; Europe -- Social conditions; Europe -- Economic conditions